Promosi Perpustakaan Melalui Kegiatan Kebun Literasi: Studi Kasus Pada Perpustakaan STAI Masjid Syuhada Yogyakarta - Sholihah, Husna Amalina; Zain, Labibah (Al-Ma mun Jurnal Kajian Kepustakawanan dan Informasi, 2025)
The literacy garden is a trial reading corner held by the Library of Sekolah Tinggi Agama Islam Masjid Syuhada (STAIMS) with the uniqueness of combining the library and nature. This is based on the large number of users who come and borrow books from the library regarding the lecture reference collection only, even though the STAIMS Library provides various other reading menus. Starting from here, libraries need to promote their collections so that they are better known to users and so that library collections are effective because they are useful for their users. This research is included in the descriptive qualitative type. Data collection techniques were carried out through participant observation and interviews. The research results show that library promotion through the Literacy Garden are very good based on the Literacy Garden receiving various support and appreciation. Books at the Literacy Garden are selected based on the criteria of interesting titles, light topics, not too thick number of pages and adapting to target visitors. The visitors regretted that the Literacy Garden only stopped here, so researchers recommended that the existence of the Literacy Garden be continued by the STAIMS Library.